Non-isothermal kinetic analysis of oil palm empty fruit bunch pellets by thermogravimetric analysis - Nyakuma, B. B. (Italian Association of Chemical Engineering - AIDIC, 2015)
The pyrolysis kinetics of oil palm empty fruit bunch (OPEFB) pellets was examined under non-isothermal conditions in a thermogravimetric (TG) analyser. Thermal analysis was carried out from 30 °C to 1,000 °C using three different heating rates 5, 10, 20 °C min-1 under nitrogen gas (N2). The TG-DTG curves showed that the pyrolysis process occurred in three steps; drying, active pyrolysis and passive pyrolysis signifying the removal of moisture, holocellulose and lignin. The pyrolysis kinetic parameters; activation energy, Ea, and frequency factor A, were deduced from the Flynn-Wall-Ozawa (FWO) model. The average Ea and A values from α = 0.10-0.60 were 160.20 kJ/mol and 1.38 × 1024 min-1. The highest Ea (231.42 kJ/mol) and A (8.27 × 1024 min-1) occurred at α = 0.30 indicating this is the slowest or rate determining step (RDS) during thermal degradation of OPEFB pellets. The average Ea for OPEFB pellets was comparably lower than cornstalk (206.40 kJ/mol), sawdust (232.60 kJ/mol) and oak (236.20 kJ/mol). The kinetic compensation or isokinetic effect was also observed during thermal decomposition of the OPEFB pellets. Hence, the results indicate OPEFB pellets can be utilized as a potential feedstock for pyrolysis.